Suriname. Significant achievements 2019 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The main activities carried out by the Institute in Suriname during 2019 are identified, with respect to the needs and interests of the country, strengthening technical capacities in climate-smart agriculture, in the use of digital technology, health and food safety, governance and operational management. Likewise, it contributed to the development of the rice industry, as well as the Rice Intensification Systems (SRI), in the beekeeping industry, the cocoa industry, and indigenous agriculture. Finally, it contributed to the inclusion of the role of women in agriculture, as well as support for gardens in orphanages, with the purpose of supplying the daily food of these institutions, without neglecting that children are trained in issues of farming.